2015
DOI: 10.1080/01457632.2015.1025003
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Heat Transfer by CuO–Water Nanofluid in Rectangular Enclosures

Abstract: This paper analyzes heat transfer and fluid flow of natural convection in inclined cavityfilled with CuO-water nanofluid and differentially heated. Conservation of mass, momentum, and energy equations are solved numerically by control volume finite element method using the SIMPLER algorithm for pressure-velocity coupling. The Prandtl number is fixed at 7.02 corresponding to water. Aspect ratio and solid volume fraction are varied from 0.5 to 4 and from 0% to 4%, respectively. The inclination angel is varied fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 19 publications
(34 reference statements)
1
9
0
Order By: Relevance
“…Ghasemi and Aminossadati [16] presented a numerical study of an inclined enclosure filled with CuO-water nanofluid and it was concluded that heat transfer could be improved by the addition of nanoparticles into the base fluid but there would be an optimum solid volume fraction that maximizes the heat transfer rate. Recently, Bouhalleb and Abbassi [18] showed similar results to those of Ghasemi and Aminossadati [16]. It was shown that the size of the nanoparticles is a more critical parameter than the concentration itself.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Ghasemi and Aminossadati [16] presented a numerical study of an inclined enclosure filled with CuO-water nanofluid and it was concluded that heat transfer could be improved by the addition of nanoparticles into the base fluid but there would be an optimum solid volume fraction that maximizes the heat transfer rate. Recently, Bouhalleb and Abbassi [18] showed similar results to those of Ghasemi and Aminossadati [16]. It was shown that the size of the nanoparticles is a more critical parameter than the concentration itself.…”
Section: Introductionsupporting
confidence: 69%
“…Nanofluids are suspensions of nano-sized solid particles in base fluids that can have higher thermal properties compared to that of base fluids, making them more efficient for heat transfer applications. Over the past years, many studies have been conducted for nanofluids for showing their better thermal properties and thermal performances as well as for understating the mechanisms of heat transport in nanofluids [13][14][15][16][17][18]. For instance, Eastman and co-authors [13] showed that a significant improvement in thermal conductivity of CuO-water nanofluid with 5% of nanocrystalline CuO particles suspended in water.…”
Section: Introductionmentioning
confidence: 99%
“…Bouhalleb and Abbassi [8] employed Control Volume-Finite Element method to study the free convection in an inclined cavity. They solved the free convection problem using Boussinesq approximation and employing the SIMPLER algorithm for velocity-pressure coupling.…”
Section: Single-phase Approachesmentioning
confidence: 99%
“…Ho et al [12] also observed the heat transfer rate enhancement with the addition of nanoparticles. Bouhalleb and Abbassi [13] carried out numerical investigation of natural convection in CuO-Water nanofluid within rectangular enclosures and ascertained that addition of CuO nanoparticles enhanced the heat transfer. Mahfoud and Bendjaghloli [14] used FVM to employ numerical investigation of natural convection in a truncated cone and found an heat transfer characteristics of cooling device by adding Cu-water nanofluid.…”
Section: Introductionmentioning
confidence: 99%